Peningkatan Hasil Belajar Materi Pecahan melalui Media Puzzle pada Kelas IV - Fausta, Agustina; Helviana, Maria; Bera, Lukas (Universitas Muhammadiyah Magelang, 2026)
This study aims to improve students’ learning outcomes in mathematics, particularly on fraction material, through the use of fraction puzzle media among Grade IVA students at SDI Maumere. The research employed a descriptive quantitative approach using a Classroom Action Research design based on the Kemmis and McTaggart model. The study was conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The research subjects were 25 Grade IVA students of SDI Maumere. Data were collected through learning achievement tests and observation sheets assessing students’ attitudes and skills. Data analysis was carried out descriptively by calculating the mean scores and the percentage of classical learning mastery in each cycle. The results showed an improvement in students’ learning outcomes after the implementation of the fraction puzzle media. The average score increased from 63.32 in the pre-cycle with 44% classical mastery to 82.24 in Cycle I with 76% mastery, and further increased to 91 in Cycle II with classical mastery reaching 92%. The improvement was observed not only in the cognitive aspect but also in students’ attitudes and skills during the learning process. These findings confirm that fraction puzzle media can be effectively used to support students’ understanding of fraction concepts and to enhance mathematics learning outcomes at the elementary school level.